The Terra Nullius of infrastructure : roads to remote Indigenous towns - Smoker, John Frank (Curtin University, 2011)
There are 287 discrete Aboriginal towns in remote areas of Western Australia, accommodating about 17,000 Aboriginal people and varying in population size from small towns with under 20 people up to larger towns with over 500 people and the population living in these areas continues to grow. These towns are subject to health issues like those of third world countries or even worse.The need for infrastructure is clear for the essential services of power, water, electricity and roads as well as the ever increasing range of the provision of other services such as education, health and medical services. The Homeland Movement which started many of these settlements in the late seventies has continued to grow into a major funding and responsibility issue for all levels of government.The history of roads associated with remote Aboriginal towns in Western Australia is a history of neglect. Despite the existence of some of these Aboriginal settlements going back 100 years, sections of the roads to these towns are still not seen as anyone’s responsibility. The newer settlements of the past thirty years of the Homeland Movement have seen many of these towns grow to being larger than many Western Australian rural towns. The fundamental issue is that the access roads (and the internal roads) to these Aboriginal towns that extend beyond the classified Main Roads and Local Roads are not legally classified and thus there is a presumption that they are not owned by anyone, there is no governance structure and therefore no one has taken responsibility for them or has allocated continuous adequate funding to service them.This thesis seeks to attribute the neglect to an underlying myth perpetuated since early settlement called the myth of terra nullius. This myth suggests that Aboriginal settlements never existed and was used to legally show why they did not need to be considered as having any rights. Perhaps this underlies the lack of certainty about these towns and the roads that lead to them. Perhaps they don’t really exist legally and so have no rights.The parallel to the concept of terra nullius is pursued in this thesis to explain this vacuum in acknowledging the existence of these roads and their governance needs. The thesis answers the question: Is the ownership and responsibility of Roads Associated with Remote Aboriginal Towns in Western Australia (WA) the terra nullius of Aboriginal infrastructure? The question is explored through an examination of the history of Aboriginal settlements and road governance in WA, and a series of case studies of settlements in the Kimberley including interviews with key stakeholders. The thesis shows through analysis of the history of attempts to create a future for Aboriginal roads as well as case studies and interviews that the idea of terra nullius seems to underlie this problem in practice.The research highlights the bilateral agreements between Commonwealth and State governments reflecting a history of neglect and inadequate policy processes for roads associated with remote Aboriginal towns. It reveals the lack of ownership and responsibility from all three levels of government and examines why this issue is still not being addressed. It also examines the use of myth making in the history of Western Australia and explores its continued use in avoiding classifying access and internal roads.The thesis then answers the questions: ‘If so, then what can be done?’ It does this by examining what has been lacking in previous governance of Aboriginal roads, proposing a new model based on Third World capacity building approaches, and by analysing the inside story of a new process to provide national Aboriginal road funding through the development of a Northern Alliance of the three ‘top end’ states and territory. In the process of developing this Alliance several case studies were found of success stories that illustrate the proposed structure for reforming the management of Aboriginal roads. This structure would not only help road funding but would develop a process for engagement, planning and employment of local Aboriginal people in maintaining their own roads.In concluding, a strategy entitled Connect, Engage and Deliver (the CED Strategy) has been proposed to address the question of how the Main Roads Department of Western Australian (and other government departments and road agencies) in partnership with Federal and local governments might seek to improve the implementation of their service and thus improve their engagement procedures with remote Aboriginal towns in order to develop lasting partnerships and a more sustainable remote Aboriginal access road network.